Generalized Analysis-oriented model of FRP confined concrete circular columns. (15th August 2021) - Shayanfar, Javad; Barros, Joaquim A.O.; Rezazadeh, Mohammadali
Abstract: This study is dedicated to the development of a generalized confinement model applicable to circular concrete columns confined by FRP full and partial confinement arrangements. To simulate the axial stress versus strain curve, a new strength model is proposed addressing the relation of axial stress and confinement pressure during axial loading, whose calibration was based on an extensive set of test results. By combining theoretical basis and experimental observations, the influence of non-homogenous distribution of concrete transversal expansibility with full/partial confinement during axial compressive loading is taken into the account in the establishment of confinement stiffness index. To estimate the ultimate condition of FRP fully/partially confined concrete, a new model with a design framework is also developed. It is demonstrated that global axial stress–strain curves and also dilation responses simulated by the proposed confinement model are in good agreement with those registered experimentally in available literature, and provides better predictions in terms of ultimate axial stress/strain than the formulations proposed by design standards.